2010
DOI: 10.1038/ki.2010.172
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Notch pathway proteins correlates with albuminuria, glomerulosclerosis, and renal function

Abstract: Recent studies indicate that the Notch signaling pathway plays an important role in diabetic kidney disease (DKD) and focal segmental glomerulosclerosis (FSGS) development, but the specificity and the clinical significance of Notch activation have not been studied in a broader set of diseases. Here we analyzed the degree of expression and localization of Notch ligands (Jagged1 and Delta1) and Notch receptors (Notch1 and Notch2) in healthy human kidneys and in biopsy samples obtained from patients with minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 32 publications
4
151
1
1
Order By: Relevance
“…Serial slices of kidney biopsy specimens were used to evaluate a correlation between the expression of cleaved Notch2 (ICN2) and the number of podocytes in each glomerulus. Consistent with a previous report 18 , the expression of ICN2 was decreased in FSGS as compared with that in MCNS (P ¼ 0.0022, Student's t-test; Fig. 6d,e).…”
Section: Articlesupporting
confidence: 81%
See 1 more Smart Citation
“…Serial slices of kidney biopsy specimens were used to evaluate a correlation between the expression of cleaved Notch2 (ICN2) and the number of podocytes in each glomerulus. Consistent with a previous report 18 , the expression of ICN2 was decreased in FSGS as compared with that in MCNS (P ¼ 0.0022, Student's t-test; Fig. 6d,e).…”
Section: Articlesupporting
confidence: 81%
“…Chen et al 17 reported that only Notch2, but not Notch1, is required for the differentiation of proximal nephron structures. In mature kidney, Murea et al 18 demonstrated that only reactivated Notch1 had a correlation with glomerulosclerosis in human glomerular diseases, while both Notch1 and Notch2 were reactivated. Thus, the function of reactivated Notch2 in glomerular diseases remains unclear.…”
mentioning
confidence: 99%
“…This was driven by a Notch-mediated downregulation of the cell cycle inhibitors p21 and p27, which forces progression toward mitosis of a cell that cannot assemble an efficient mitotic spindle, because it poorly expresses Aurora kinase B [75]. Interestingly, Notch expression is virtually absent in glomeruli of healthy adult kidneys, while several studies demonstrated strong Notch upregulation in podocytes of patients affected by several types of glomerular disorders characterized by podocyte death [75, 77, 78]. In addition, persistent activation of Notch in podocytes leads to podocyte loss and FSGS [75].…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…Pretreatment of renal epithelial cells with LXA 4 (1 nM; 30 minutes) attenuated TGF-b1-induced CDH2, FN1, and JAG1 protein expression ( Figure 1, B and C). Notch signaling is an important driver of renal fibrosis, 19,20 and it is noteworthy that LXA 4 suppressed TGF-b1 driven expression of the Notch ligand JAG1 and its target gene, hairy and enhancer of split 1 (HES1), which is also associated with renal fibrosis (Figure 1D). 21 LXA 4 attenuated TGF-b1 induction of numerous profibrotic genes including FN1, COL1A1, COL1A2, and THBS1 ( Figure 1D).…”
Section: Lxa 4 Attenuates Tgf-b1 Responses Of Renal Epitheliamentioning
confidence: 99%